Perencanaan Arsitektur Sistem Informasi Menggunakan Metode Enterprise Architecture Planning di CV. Furqon Buana Gemilang - Rachman, Tonton Taufik; Rohmat, Aji (Ma'soem University, 2024)
CV. Furqon Buana Gemilang currently does not have an architectural plan so that the business processes that occur are still not optimal. CV. Furqon Buana Gemilang has business process activities, such as Tour & Travel which are in the form of processes in selling airline tickets, vacation programs, hotel reservations, and outbound. In its marketing process, it only uses social media such as Instagram and WhatsApp as the main media in promoting this travel product brand. And for the website, it is still in the development process and has not been able to fully process. The modeling used in the architectural planning to be made is by using the Enterprise Architecture Planning (EAP) method which consists of several stages starting from initialization of planning, business modeling, current systems and technologies, data architecture, application architecture, technology architecture, and implementation plans. This research will produce information system architecture planning at CV. Furqon Buana Gemilang Cikancung using the Enterprise Architecture Planning method which includes 7 stages. In the Company's business process there are 5 main activities, namely airline ticket sales, vacation programs, hotel reservations, outbound, and consumer services, as well as 3 supporting activities, namely HR management, financial management, and information system development. With this architectural planning, the Company can follow the stages and schedules designed to ensure that the implementation runs in a structured manner.